KOMUNIKASI THERAPEUTIC COMMUNITY PASIEN PENYALAHGUNA NARKOBA DIMASA PANDEMI COVID-19 - Laila Zakiyatu Zahro; Rama wijaya Kesuma Wardani; Pasiska Pasiska (Jurnal Bimbingan Penyuluhan Islam, 2021)
This study will examine the Therapeutic Community Communication of Drug Abuse Patients during the Covid-19 Pandemic "at the Karunia Insani Foundation Rehabilitation Center, Kab. Musi Rawas, as for the research method used, namely qualitative research which approach is more to field research, the data collection techniques through interviews, documentation and observation, then the data is reduced so as to obtain the validity of research that can be accounted for scientifically, as for the results of In this research, the application of the therapeutic community method, the formation of Behavioral Menegement Shaping, which prioritizes drug abusing patients, knows all program activities every day and follows disciplined discipline This application is carried out during the morning meeting, therapeutic community support during the Covid-19 pandemic has three directions. , namely peer pressure in the form of a warning when making a mistake and giving a response (feedback) in the form of solutions and motivation when listening to problems and complaints between drug abuse patients, family visits, namely when families visit patients drug abuse to see the development that is in them, even though it is limited, drug abuse patients feel and feel more comfortable, lastly, from the gift of human rehabilitation institution, they hold recreation (outing) once a month, but when the Covid-19 pandemic this activity stops temporarily and will done again after the covid-19 pandemic has not increased much.